(untitled) (Journal of Social Sciences Review, 2025)
The objective of the study is to examine the association between psychological distress—operationalized as depression, anxiety, and stress—among caregivers in Pakistan of individuals with Alzheimer. Using a cross-sectional correlational design and purposive sampling, data were Collected from 250 caregivers. The results revealed a significant positive association between stress, anxiety, and depression. Hayes’ Macro Process 4.1, Model 4, demonstrated that anxiety significantly and positively mediates the association between stress and depression. The findings were discussed in relation to existing literature and practical recommendations were provided to enhance caregiver well-being. These include offering counselling services, raising awareness about Alzheimer’s disease, encouraging peer support networks, promoting access to professional mental health care, providing guidance on effective caregiving strategies, and emphasizing the importance of establishing government-run programs and support groups for Alzheimer’s caregivers.